2014
DOI: 10.1038/srep05727
|View full text |Cite
|
Sign up to set email alerts
|

Mirror-symmetric Magneto-optical Kerr Rotation using Visible Light in [(GeTe)2(Sb2Te3)1]n Topological Superlattices

Abstract: Interfacial phase change memory (iPCM), that has a structure of a superlattice made of alternating atomically thin GeTe and Sb2Te3 layers, has recently attracted attention not only due to its superior performance compared to the alloy of the same average composition in terms of energy consumption but also due to its strong response to an external magnetic field (giant magnetoresistance) that has been speculated to arise from switching between topological insulator (RESET) and normal insulator (SET) phases. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…There have been a number of experimental demonstrations of the CSL memory567891011, but the switching mechanism is so far not fully defined at an atomic level. There have been several suggestions to explain how the atoms are manipulated, including charge injection12, electric field613, magnetic field6, thermal activation7 and polarization dependent optical control14.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There have been a number of experimental demonstrations of the CSL memory567891011, but the switching mechanism is so far not fully defined at an atomic level. There have been several suggestions to explain how the atoms are manipulated, including charge injection12, electric field613, magnetic field6, thermal activation7 and polarization dependent optical control14.…”
mentioning
confidence: 99%
“…There have been several suggestions to explain how the atoms are manipulated, including charge injection12, electric field613, magnetic field6, thermal activation7 and polarization dependent optical control14. However, the atomic structures of the low resistance state (LRS) and high resistance states (HRS) are still not fully agreed by different groups, so the atomic mechanism needs further definition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, several superlattice structures including GeTe/Sb 2 Te 3 have been theoretically predicted to exhibit unusual properties forming topological insulators or Dirac semimetals, leading to the experimental confirmation of unusual magnetic properties despite the lack of magnetic elements. [12][13][14][15] The most widely used techniques to fabricate 2D chalcogenides are exfoliation from a bulk single crystal, chemical vapor deposition (CVD), and molecular beam epitaxy (MBE). [16][17][18][19][20][21] However, the area of films that can be fabricated by exfoliation is limited and sample sizes are not uniform.…”
mentioning
confidence: 99%
“…These reports suggested that the switching was due to vertical displacements of Ge atoms at the interface of GeTe layers and Sb 2 Te 3 layers in the superlattice. The driving force of the Ge displacements has been attributed to charge injections, 9 electric field, 10 thermal activation, 11 and stresses in the superlattice films. 12,13 However, we need to clarify whether these displacements occurred in all interfaces in the superlattice, in a part of the interfaces, or in other regions.…”
mentioning
confidence: 99%